Business in practice: self-reflection and performance analysis of relyon - Spengler, Alisa Carina (2022)
Business in Practice consists of the professional experiences gained during a simulation, as well as the personal development within this period. The roles of Strategy, Marketing, Finance, Operations, and Human Resources are highlighted and obtained by one group member. The focus was set on working together in cross-functional teams to achieve the best possible outcome for a fictive car manufacturer. Overcoming personal milestones (such as applying effective-decision making) and various business challenges (such as the transition to e mobility) enriched the project. Both delivered insights in a company, emphasized the interconnectivity between all departments, and functioned as preparation for upcoming career paths.